Professional Negligence by Quantity Surveyors - Tan, Chai San (2015)
Professional negligence is a failure to perform standard duty of care by the person who is known to be skilful. Quantity surveyors involved in the construction process from the start to the end. He is said to be owed a duty of care to the parties involved in the contract and also owed a duty of care to third parties under tort. This research is to identify the conducts of quantity surveyors that will lead to professional negligence and to discover remedies for professional negligence. This research is conducted in quantitative method, which is questionnaire survey. The results are obtained from 31 respondents who are working in Consultant Quantity Surveyors Firm in Selangor Malaysia. Based on their responds, the analysis of the conducts of Quantity Surveyors is tabulated. The result shown that the top 3 conducts of Quantity Surveyors that will lead to professional negligence arc: (I) Preparation of Preliminary Estimates. (2) Tender Documents, (3) Estimate for Variation Works. From the analysis, the most preferable remedy for professional negligence is Professional Indemnity Insurances (Pl). The finding of the result showed that the professional negligence by quantity surveyors is much related to costing works.